Adsorption contributions of graphene to sodium ion storage performance. (25th April 2018) - Fu, Hao; Xu, Zhanwei; Guan, Weiwei; Shen, Xuetao; Cao, Liyun; Huang, Jianfeng
Abstract: Graphene derivates, including graphite, graphene oxide (GO), and reduced graphene oxide (rGO), are employed as sodium ion battery anodes to investigate the effect of adsorption reactions on their electrochemical performance. GO and rGO exhibit the reversible capacity of 230, 192 mAh g −1 at a low current density of 100 mA g −1 . However, when tested at higher current densities of 200, 500, and 1000 mA g −1, the GO electrodes deliver 136, 76, and 38 mAh g −1, respectively. As a comparison, rGO exhibits capacity as high as 168, 133, and 117 mAh g −1 at the same conditions—23.5%, 75.0%, and 207.9% higher, respectively, than the capacities of GO. These analyses, based on the cyclic voltammetry curves, discharge/charge voltage profiles, rate and cycle performance, as well as infrared spectroscopy analysis, show the contributions of the capacity from reversible physical and chemical adsorption. The main behavior type of rGO is physical adsorption, which meets the requirements of the fast charge/discharge process, while the predominant behavior of GO is chemical adsorption.